C-Reactive Protein Promotes the Expansion of Myeloid Derived Cells With Suppressor Functions - Jimenez, Rachel V.; Kuznetsova, Valeriya; Connelly, Ashley N.; Hel, Zdenek; Szalai, Alexander J. (Frontiers in Immunology, 2019)
Previously we established that human C-reactive protein (CRP) exacerbates mouse acute kidney injury and that the effect was associated with heightened renal accumulation of myeloid derived cells with suppressor functions (MDSC). Herein we provide direct evidence that CRP modulates the development and suppressive actions of MDSCs in vitro. We demonstrate that CRP dose-dependently increases the generation of MDSC from wild type mouse bone marrow progenitors and enhances MDSC production of intracellular reactive oxygen species (iROS). When added to co-cultures, CRP significantly enhanced the ability of MDSCs to suppress CD3/CD28-stimulated T cell proliferation. Experiments using MDSC from FcγRIIB deficient mice (FcγRIIB‒/‒) showed that CRP’s ability to expand MDSCs and trigger their increased production of iROS was FcγRIIB-independent, whereas its ability to enhance MDSC’s T cell suppressive action was FcγRIIB-dependent. Importantly, CRP also enabled freshly isolated primary human neutrophils to suppress proliferation of autologous T cells. These findings suggest that CRP might be an endogenous regulator of MDSC numbers and actions in vivo.